Chinese Elements in Persian Paintings - Dastan, Nasrin. author. aut Link
XXXII, 194 p. 143 illus., 136 illus. in color.
Keywords: This book describes the fruit of the establishment of the Yili Khanate by the Mongols in the Asian and European civilization, which is linked by the ancient Silk Road-fine paintings. Persian painters combine the techniques of Chinese painting with their own unique artistic views to enrich fine paintings according to their own taste and interests. By analyzing the illustration styles and techniques in the Collection of History and the Chronicles of Kings, this book describes the influence of Chinese book prints on the fine painting of Iranian manuscripts. Nasrin Dastan, Ph.D. History of Chinese Arts (Han &Tang dynasty) Central Academy of Fine Arts.Now she is Assistant Professor & Head of Oriental Arts Department in Institute of Arts Studies &Academic Research (IASAR)Iranian Academy of Art.The published works are Chinese Elements in Persian Paintings,Art of Dunhuang Caves and Artistic relation through the Silk road,etc.